2019
DOI: 10.3855/jidc.11441
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M-producing Escherichia coli Isolated from urban pigeons (Columba livia domestica) in Brazil

Abstract: Introduction: Worldwide urban pigeons (Columba livia domestica) are an important reservoir of pathogenic and multidrug-resistant bacteria (MDR). Plasmids are key genetic elements in the dissemination of antimicrobial drug resistance in bacteria, including beta-lactams and quinolones, which are the most important classes of drugs for treatment of Enterobacteriaceae infections in human and veterinary medicine. The aim of this study was to determine the presence of Escherichia coli (E. coli) harboring plasmids co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The carriage of ESBL producers in pigeons in our study was comparable to previous studies around the world, which have reported the detection of E. coli isolates harbouring bla CTX-M genes from pigeons, including Bangladesh, France, Germany, Nicaragua, China, and Brazil [ 9 , 10 , 34 , 35 , 40 , 41 ]. In this study, we also detected the bla OXA-48 gene in E. coli isolates from different urban places around the city, including a sewage treatment plant, a university, and a public park.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The carriage of ESBL producers in pigeons in our study was comparable to previous studies around the world, which have reported the detection of E. coli isolates harbouring bla CTX-M genes from pigeons, including Bangladesh, France, Germany, Nicaragua, China, and Brazil [ 9 , 10 , 34 , 35 , 40 , 41 ]. In this study, we also detected the bla OXA-48 gene in E. coli isolates from different urban places around the city, including a sewage treatment plant, a university, and a public park.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of multi-drug resistant bacteria in pigeons is generally linked to faecal contamination of both human and animal origin [ 7 ]. Carriage of such bacteria in pigeon faeces has been reported in different countries, with much of the focus being on Escherichia coli species [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, clonal plasmids carrying blaCTX-M genes are largely restricted to animals (6,8,22,24). Moreover, blaCTX-M genes in this group are mainly associated with I1 plasmids (6,8,22,25,26), and not reported from F plasmids which are the dominant plasmid type overall in E. coli. Therefore, blaCTX-M genes of this group may seldom exchange blaCTX-M genes with other plasmids.…”
Section: Methodsmentioning
confidence: 79%
“…It was previously shown that pigeons are reservoir of multidrug-resistant E. coli , including ESBL-producing strains ( 17 19 ). Cunha et al ( 20 ) found that feral pigeons carried ESBL-positive E. coli strains producing the enzymes CTX-M-2 and CTX-M-8 ( 20 ).…”
Section: Discussionmentioning
confidence: 99%